2020
DOI: 10.21203/rs.3.rs-32854/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted inhibition of β-catenin alleviates airway inflammation and remodeling in asthma via modulating the profibrotic and anti-inflammatory actions of transforming growth factor-β1

Abstract: Background and objective TGF-β1 is a key cytokine involved in airway inflammation and airway remodeling in asthma, owing to its anti-inflammatory and profibrotic effects. In our previous study, we found that the knockdown of cytosolic β-catenin mitigated the profibrogenic effect of TGF-β1 without affecting its anti-inflammatory effect. However, the exact role of targeting β-catenin in asthma is not yet fully demonstrated. In the present study, we investigated the effect and mechanism of targeting β-catenin in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…AIT increases secretoglobin 1A1 expression in cells of the lower airways from patients with allergic asthma to improve airway inflammatory response (34). It also suppresses TGF-β1 in asthma airway epithelial cells, which regulate airway inflammation and remodeling in asthma due to its anti-inflammatory and profibrotic effect (35,36). Similarly, our study showed that Alutard SQ inhibited the HDM-induced TGF-β1 protein secretion, and airway inflammation.…”
Section: Discussionsupporting
confidence: 57%
“…AIT increases secretoglobin 1A1 expression in cells of the lower airways from patients with allergic asthma to improve airway inflammatory response (34). It also suppresses TGF-β1 in asthma airway epithelial cells, which regulate airway inflammation and remodeling in asthma due to its anti-inflammatory and profibrotic effect (35,36). Similarly, our study showed that Alutard SQ inhibited the HDM-induced TGF-β1 protein secretion, and airway inflammation.…”
Section: Discussionsupporting
confidence: 57%
“…As one of the gelatin enzymes, MMP-9 binds to CD44 to release stored TGF-β1, which may participate in the remodeling of respiratory tract and lung, such as asthmatic airway remodeling. In addition, OVA-sensitized MMP-2, MMP-8, MMP-9 and MMP-12 in the lung tissue of obese mice were imbalanced, accompanied by high degradation, resulting in excessive deposition of type I and Type III collagen in the lung stroma of obese animals (Vieira and de Oliveira et al, 2020;Huo and Tian et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…e critical target of corn silk, CTNNB1 (β-catenin), is a member of the cyclic catenin family, whose primary role is to regulate adhesion between cells and intercellular substances. In addition, some studies have indicated that activation of the canonical Wnt-1/β-catenin pathway regulates the immune response and induces appropriate T cell responses [32]. YWHAG and YWHAZ belong to the YWHA protein family.…”
Section: Discussionmentioning
confidence: 99%